BAC libraries from wheat chromosome 7D: efficient tool for positional cloning of aphid resistance genes - Simková, Hana; Safář, Jan; Kubaláková, Marie; Suchánková, Pavla; Cíhalíková, Jarmila; Robert-Quatre, Heda; Azhaguvel, Perumal; Weng, Yiqun; Peng, Junhua; Lapitan, Nora L V; Ma, Yaqin; You, Frank M; et al. (Journal of biomedicine & biotechnology, 2011)
Positional cloning in bread wheat is a tedious task due to its huge genome size and hexaploid character. BAC libraries represent an essential tool for positional cloning. However, wheat BAC libraries comprise more than million clones, which makes their screening very laborious. Here, we present a targeted approach based on chromosome-specific BAC libraries. Such libraries were constructed from flow-sorted arms of wheat chromosome 7D. A library from the short arm (7DS) consisting of 49,152 clones with 113 kb insert size represented 12.1 arm equivalents whereas a library from the long arm (7DL) comprised 50,304 clones of 116 kb providing 14.9x arm coverage. The 7DS library was PCR screened with markers linked to Russian wheat aphid resistance gene DnCI2401, the 7DL library was screened by hybridization with a probe linked to greenbug resistance gene Gb3. The small number of clones combined with high coverage made the screening highly efficient and cost effective.
Keywords: Triticum; přirozená imunita; Chromosomes, Artificial, Bacterial; Genes, Plant; polymerázová řetězová reakce; umělé bakteriální chromozomy; karyotypizace; mikrosatelitní repetice; Cloning, Molecular; klonování DNA; Karyotyping; mšice; pšenice; hybridizace nukleových kyselin; chromozomy rostlin; Chromosomes, Plant; Immunity, Innate; nemoci rostlin; Fluorescence; Microsatellite Repeats; Animals; zvířata; Aphids; Plant Diseases; Polymerase Chain Reaction; rostlinné geny; Nucleic Acid Hybridization; fluorescence